Lopinavir-Ritonavir Impairs Adrenal Function in Infants. (21st October 2019) - Kariyawasam, Dulanjalee; Peries, Marianne; Foissac, Frantz; Eymard-Duvernay, Sabrina; Tylleskär, Thorkild; Singata-Madliki, Mandisa; Kankasa, Chipepo; Meda, Nicolas; Tumwine, James; Mwiya, Mwiya; Engebretsen, Ingunn; Flück, Christa E; et al.
Abstract: Background: Perinatal treatment with lopinavir boosted by ritonavir (LPV/r) is associated with steroidogenic abnormalities. Long-term effects in infants have not been studied. Methods: Adrenal-hormone profiles were compared at weeks 6 and 26 between human immunodeficiency virus (HIV)-1–exposed but uninfected infants randomly assigned at 7 days of life to prophylaxis with LPV/r or lamivudine (3TC) to prevent transmission during breastfeeding. LPV/r in vitro effect on steroidogenesis was assessed in H295R cells. Results: At week 6, 159 frozen plasma samples from Burkina Faso and South Africa were assessed (LPV/r group: n = 92; 3TC group: n = 67) and at week 26, 95 samples from Burkina Faso (LPV/r group: n = 47; 3TC group: n = 48). At week 6, LPV/r-treated infants had a higher median dehydroepiandrosterone (DHEA) level than infants from the 3TC arm: 3.91 versus 1.48 ng/mL ( P < .001). Higher DHEA levels (>5 ng/mL) at week 6 were associated with higher 17-OH-pregnenolone (7.78 vs 3.71 ng/mL, P = .0004) and lower testosterone (0.05 vs 1.34 ng/mL, P = .009) levels in LPV/r-exposed children. There was a significant correlation between the DHEA and LPV/r AUC levels (ρ = 0.40, P = .019) and Ctrough (ρ = 0.40, P = .017). At week 26, DHEA levels remained higher in the LPV/r arm: 0.45 versus 0.13 ng/mL ( P = .002). Lopinavir, but not ritonavir, inhibited CYP17A1 and CYP21A2 activity in H295R cells. Conclusions: Lopinavir was associated with dose-dependent adrenal dysfunction in infants. The impact of long-term exposure and potential clinical consequences require evaluation. Clinical Trials Registration: NCT00640263 Abstract : Giving lopinavir to infants during their first year of life induces early, asymptomatic adrenal disruption compatible with the combined inhibition of CYP 21 and CYP 17 enzymes. The impact of prolonged treatment on the adrenal glands may require further attention.